2020
DOI: 10.1186/s40360-020-00410-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PI3K/AKT molecular pathway mediated by membrane estrogen receptor GPER accounts for cryptotanshinone induced antiproliferative effect on breast cancer SKBR-3 cells

Abstract: Background: Breast cancer is the most frequently diagnosed malignancy among women and the second leading cause of cancer death worldwide. Among which nuclear estrogen receptor (nER) negative breast cancer is always with much poor prognosis. Recently, membrane G protein coupled estrogen receptor (GPER), a newly recognized estrogen receptor has been documented to take essential part in the development and treatment of breast cancer. The present study was designed to investigate the anti nER negative breast cance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…CT inhibits PI3K/Akt pathway in a doseā€ and timeā€dependent manner. Also, inhibitory effect of CT on PI3K/Akt leads to stimulation of cell cycle arrest at G1 phase (Shi et al, 2020). IGFā€1R, as a upstream mediator, induces PI3K/Akt signaling pathway, while NFā€kB is a downā€stream target of PI3K/Akt that ensure proliferation of cancer cells.…”
Section: Cryptotanshinone As a Modulator Of Molecular Pathways In Difmentioning
confidence: 99%
“…CT inhibits PI3K/Akt pathway in a doseā€ and timeā€dependent manner. Also, inhibitory effect of CT on PI3K/Akt leads to stimulation of cell cycle arrest at G1 phase (Shi et al, 2020). IGFā€1R, as a upstream mediator, induces PI3K/Akt signaling pathway, while NFā€kB is a downā€stream target of PI3K/Akt that ensure proliferation of cancer cells.…”
Section: Cryptotanshinone As a Modulator Of Molecular Pathways In Difmentioning
confidence: 99%
“…In addition, CPT induced apoptosis in SKBR-3 ER-negative but G protein-coupled estrogen receptor (GPER)-positive breast cancer cells ( Shi et al, 2019 ). Further study confirmed that CPT did restrain SKBR-3 cell growth in a time- and dose-dependent manner ( Shi et al, 2020 ). According to recent studies, the inhibitory effect of CPT on the proliferation and migration of MCF-7 cells is much higher than on those of MDA-MB-231 cells, suggesting its effect was associated with ER expression ( Chen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 83%
“…Phosphorylation of ERK is required for the binding of ER to the IGFāˆ’1 receptor [ 37 ]. In addition, the PI3K and p āˆ’AKT pathways are mediated by membrane G proteināˆ’coupled estrogen receptors [ 38 ]. In the present study, p āˆ’ERK and p āˆ’AKT levels were increased when S. aureus EVs were used in combination with tamoxifen compared to tamoxifen treatment alone.…”
Section: Discussionmentioning
confidence: 99%